Barriers Faced In Cloud Computing Adoption - Masood, Isra; Bhardwaj, Ankur; Verma, Pushpneel (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing is the next generation of internet-based comprehensive computing systems which in it, the computing resources are provided “as a service”. Cloud computing is an important structure with great potential in lessening the costs by recuperating and developing functionality and cost-effective outcome which in turn can increase cooperation, rate and scalability acceptance to comprehensible degree. This technology has provide large organizations and IT companies with lots of opportunities in developed countries but these opportunities face many challenges and barriers which is one of the main concerns in cloud computing field. This paper focuses on a range of considered issues from a broad cross section of areas of expertise required to ensure a successful cloud computing adoption. It presents in detail the various factors which are key to a successful cloud computing adoption. It also explains how the prominence on collaboration between clients and vendor is necessary for successful adoption of cloud computing. If the organisation feels free, confident and secure to use cloud services then it is more likely that the adoption rate will increase. As Cloud Computing is referred to both the applications delivered as services over the Internet and the infrastructures (i.e., the hardware and systems software in the data centres) that provide those services , we present the security concerns in terms of the diverse applications and infrastructures. More concerns on security issues, such as availability, confidentiality, integrity control, authorization and so on, should be taken into explanation. The rest of the paper will be organized as highlighting the basic cloud computing definitions and architecture, presenting the barriers and challenges to adoption of cloud computing and then the paper will be concluded along with the future research scope.